2009
DOI: 10.1038/nature08268
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and oncogene rescue of metabolic defects caused by loss of matrix attachment

Abstract: Normal epithelial cells require matrix attachment for survival and the ability of tumour cells to survive outside their natural extracellular matrix (ECM) niches is dependent on acquisition of anchorage independence1. While apoptosis is the most rapid mechanism for eliminating cells lacking appropriate ECM attachment2, recent reports suggest that non-apoptotic death processes prevent survival when apoptosis is inhibited in matrix-deprived cells3 , 4. Here we demonstrate that detachment of mammary epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
996
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 925 publications
(1,073 citation statements)
references
References 35 publications
48
996
2
1
Order By: Relevance
“…Previous studies have revealed a role for the ERK/MAPK pathway in the evasion of anoikis. 21,24,27,32 In order to assess the activation of ERK signaling in IBC cells, we examined phospho-ERK levels in KPL-4 cells deficient in ErbB2 or SUM149 cells deficient in EGFR. In each case, we discovered that the deficiency in receptor tyrosine kinase expression (i.e., ErbB2 in KPL-4 and EGFR in SUM149) resulted in a concomitant loss of phospho-ERK (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have revealed a role for the ERK/MAPK pathway in the evasion of anoikis. 21,24,27,32 In order to assess the activation of ERK signaling in IBC cells, we examined phospho-ERK levels in KPL-4 cells deficient in ErbB2 or SUM149 cells deficient in EGFR. In each case, we discovered that the deficiency in receptor tyrosine kinase expression (i.e., ErbB2 in KPL-4 and EGFR in SUM149) resulted in a concomitant loss of phospho-ERK (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps this defect could be overcome through changes in glucose or fatty acid metabolism that have previously been reported in ECM-detached cells. 24,48 Thus it will be especially important to examine metabolic changes in IBC cells to understand how these cells deal with metabolic needs during ECM detachment. Nonetheless, the data presented here provide significant and novel insight into the molecular mechanisms utilized by IBC cells to survive in the absence of ECM attachment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results, however, indicate that the underlying metabolic transition (the Warburg transition) could be essential for cancer cells to survive outside their natural extracellular matrix (ECM) niches. Rerouting of the carbohydrate flux from glycolysis to the pentose phosphate pathway (PPP) is essential for survival of detached cells and is independent of their energy status [56].…”
Section: Reviewmentioning
confidence: 99%
“…The impact is so effective that 15 lM DIOS restore completely the intracellular ATP levels. Since ATP synthesis can be influenced by the oxidative status of the cells [46] antioxidant effect of DIOS was also tested applying the same conditions. 15 lM OTA caused an about 60% increase of ROS production (Fig.…”
Section: Diosmetin Versus Atp Depleting Effect Of Ochratoxin Amentioning
confidence: 99%